Long-term outcomes of major trauma with unstable open pelvic fractures: A population-based cohort study. (April 2021) - Gabbe, Belinda J; Stewart, Ian; Veitch, William; Beck, Ben; Cameron, Peter; Russ, Matthias; Bucknill, Andrew; Steiger, Richard de; Esser, Max
Aims: The aims of this study were to describe the profile and longer-term outcomes of major trauma patients with unstable open pelvic fractures. Patients and methods: An observational study was performed using data from the population-based Victorian State Trauma Registry. Adult (≥16 years) major trauma patients who had sustained an unstable open pelvic fracture between 1 July 2010 and 30 June 2017 in Victoria (Australia) were included. Patient demographics, injury event, severity and management data were extracted. Patients were followed up at 6, 12 and 24 months post-injury to collect information about health status, function and return to work. Results: There were 67 patients. The mean (SD) age was 41.4 (18.3) years, and 66% were male. Seventy-six per cent were road traffic injuries, 96% were managed at Level 1 trauma centres and all were multi-trauma patients. A third were Tile C fractures and 80% underwent surgical stabilisation of the pelvic injury. Eighty per cent were admitted to intensive care. The in-hospital mortality rate was 9%. Most (89%) survivors were discharged to an inpatient rehabilitation facility. The proportion classified as 'severe disability' on the Glasgow Outcome-Scale Extended declined from 38% at 6 months to 19% at 24 months. The overall three-level EuroQoL five-dimensional instrument score increased with time indicating better health status, and 50% of patients returned to work by 24 months. Conclusions: Major trauma with unstable, open pelvic fracture is rare. Low in-hospital mortality was observed. Most survived to hospital discharge and outcomes improved with time post-injury, but 75% of patients experienced persistent pain and ongoing mobility and activity restrictions.